The Evolutionarily Conserved Serine Residues in BRI1 LRR Motifs Are Critical for Protein Secretion - Chen, Tianshu; Wang, Bin; Wang, Fangfang; Niu, Guanting; Zhang, Shuo; Li, Jianming; Hong, Zhi (Frontiers in Plant Science, 2020)
As a well-studied leucine-rich-repeat receptor-like kinases (LRR-RLKs) in Arabidopsis (Arabidopsis thaliana), BRI1 functions as a cell surface receptor for sensing the smallest ligand molecule identified thus far. The weak allele bri1-9 (S662F) harbors a mutation at the conserved serine (Ser*) residue among 25 LRRs, which leads to the protein retention in the ER. However, very little is known about the importance of these residues. Through site-directed mutagenesis and a phenotypic complementation test, we examined the effects of these conserved serine residues (S*-chain) on protein secretion and functions. The results showed that the replacements of these serine residues significantly changed the sub-localization of BRI1-GFPs to the ER and that rigid space constraints, as well as the requirement of successive inner polar contacts, affect these sites. In addition, the continuous presence of Ser* is mainly disrupted at the LRR-island domain interface, and the changes of these four nonserine residues to serine greatly decreased the protein ability to complement bri1-301 compact phenotype and the BR signaling activation. The sequence alignment revealed that other known LRR-RLK also harbors the S*-chain and the non-Ser* residues at the ligand-binding region along the S*-chain, which confirms the evolutionary significance of residues at these sites in plant LRR-RLKs.